The Digital Chains of Modern Slavery: A Study of Human Trafficking in Central Europe - Rau , Marcin (The ECHR at 70: The Central European Narrative, 2025)
This comprehensive analysis explores the multifaceted issue of human trafficking in the digital era, with a special focus on Hungary and Poland. The article examines how traffickers exploit vulnerable groups, including economic migrants and ethnic minorities, by harnessing the power of artificial intelligence (AI) and social media. It contrasts the approaches of Hungary, which tends to prioritise criminal groups, with Poland’s struggles with systemic inefficiencies in victim identification and prosecution. The article further delves into the sophisticated use of digital platforms and AI by traffickers to manipulate and control victims, and the challenges law enforcement faces in adapting to these new technological advancements. Emphasizing the need for international cooperation and a proactive approach, the article highlights the significance of educating the younger generation on the risks associated with social media and AI, underscoring the importance of cybersecurity awareness in combatting human trafficking. Keywords: Human Trafficking, Digital Era, Hungary, Poland, Artificial Intelligence,Social Media